PENGALAMAN REMAJA PEMAIN GAME ONLINE DALAM MEREGULASI EMOSI: STUDI KASUS DI MTs ROUDLOTUL FURQON - Mazada Hafidhotuzzahro; Nurul Aulia Dewiana; Awalia Zahra Arliza (JURNAL ILMIAH RESEARCH STUDENT, 2026)
. Advancements in digital technology have increased the time adolescents spend playing online games to between two and four hours daily; while this offers entertainment, it often triggers negative emotions such as anger, disappointment, and frustration stemming from losses or network disruptions. This study aims to explore in depth the emotional regulation experiences of adolescent online gamers at MTs Roudlotul Furqon and to examine how these experiences interact with moral values ​​within the madrasah environment. Employing a qualitative case study approach involving in-depth interviews, the research reveals that these adolescents employ various adaptive strategies to stabilize their emotions, ranging from stopping the game, taking breaks, and listening to music, to engaging in spiritual practices such as performing wudhu (ablution) and prayer. Successful emotional regulation is strongly supported by parental roles in limiting playtime and by teacher guidance through school-based religious activities. Ultimately, the ability to control emotions has a positive impact on maintaining harmonious social relationships and sustaining the adolescents' academic focus.